2008
DOI: 10.1089/fpd.2007.0035
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of the Microbiological Quality of Feral Pig Carcasses Processed for Human Consumption in Queensland, Australia

Abstract: An investigation of the microbiological quality of 217 feral pig carcasses at a Queensland wild game processing plant was carried out using the excision method of sampling. Samples were analyzed for aerobic plate count (APC), E. coli, and Salmonella over a period of 2 years. The mean adjusted APC was 4.7 log colony-forming units (CFU)/g, and counts at the 90th, 95th, and 99th percentiles were 4.8, 5.2, and 6.1 log CFU/g, respectively. The maximum number of bacteria recovered was 6.4 log CFU/g, and the limit of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 7 publications
1
7
0
Order By: Relevance
“…Feral pig meat has become an alternative to the consumption of wild boar meat in some countries because of its organoleptic profiles, such as its strong flavour and dark colour [99]. As described in Table A2, feral pig carcasses obtained from a Queensland wild game processing plant between June 2004 and June 2006 were found to contain Salmonella using a polymerase chain reaction (PCR) [100]. This study illustrated that the low level of Salmonella contamination in the feral pig carcasses could arise from the implementation of hazard analysis and critical control point (HACCP)-based national quality assurance programmes, as defined by the Codex Alimentarius Commission [101].…”
Section: Queenslandmentioning
confidence: 99%
See 1 more Smart Citation
“…Feral pig meat has become an alternative to the consumption of wild boar meat in some countries because of its organoleptic profiles, such as its strong flavour and dark colour [99]. As described in Table A2, feral pig carcasses obtained from a Queensland wild game processing plant between June 2004 and June 2006 were found to contain Salmonella using a polymerase chain reaction (PCR) [100]. This study illustrated that the low level of Salmonella contamination in the feral pig carcasses could arise from the implementation of hazard analysis and critical control point (HACCP)-based national quality assurance programmes, as defined by the Codex Alimentarius Commission [101].…”
Section: Queenslandmentioning
confidence: 99%
“…1 Cultural [ 79 ] Goat carcasses 121 28.90 Saintpaul Typhimurium Chester Agona Cultural [ 97 ] Feral pig carcasses 217 1.38 Salmonella spp. Automated PCR [ 100 ] Frozen chicken nuggets 300 batch 8.70 Salmonella subsp. I Salmonella subsp.…”
Section: Table A1mentioning
confidence: 99%
“…The most common isolates were serotypes Salmonella enterica serovars Anatum, Typhimurium and Havana. In contrast, in a 2-year investigation of the microbiological quality of 217 pig carcasses at a Queensland wild game processing plant, Eglezos et al (2008) detected Salmonella in only 1.4% of samples and no significant relationship (p > 0.05) was detected between season and Salmonella prevalence. The culture of fresh faecal and lymph node samples from wild pigs in Australia for Salmonella has apparently not been reported in the peer-reviewed literature.…”
Section: Introductionmentioning
confidence: 79%
“…Montagnaro et al, 2010;Vengust et al, 2006;Vicente et al, 2002;Vieira-Pinto et al, 2011;Wacheck et al, 2010;Wisniewski, 2001), but also in the United States (Thakur et al, 2011) and in Australia (Bensink et al, 1991;Eglezos et al, 2008). In Australia, only studies of carcass sampling for Salmonella have been published in the peer-reviewed literature.…”
Section: Introductionmentioning
confidence: 99%
“…An epidemiologic study of brucellosis trends in Florida revealed 6 human cases among feral swine hunters (Bigler et al 1977). A recent survey of feral swine carcasses processed in Australia identified low levels of Salmonella contamination (Eglezos et al 2008). These findings underscore the importance of following proper handling and cooking procedures when field dressing or preparing wild game meat.…”
Section: Food Safety Issues and Feral Swinementioning
confidence: 88%